Analysis of Knowledge-based Economy Development in Poland in the Light of Strategic Documents - Dworak, Edyta (Comparative Economic Research. Central and Eastern Europe, 2012)
After the European Union summit in spring 2005, the member countries were obliged to implement the Lisbon Strategy on the national level and to prepare national strategies to fulfil its goals. Due to this, the goals and tasks of building knowledge-based economy were entered into the strategic documents and operational programs included in the National Strategic Reference Framework 2007-2013 (NSRF), prepared by successive governments after 2005. However, it needs to be mentioned that also scientific institutions (e.g. the Polish Academy of Sciences, PAN) introduced various strategic documents in which issues of knowledge-based economy and its role in the social and economic development of Poland were included. However, a study of a holistic knowledgebased economy was not made. The aim of article is to present and assess the most important documents referring to the strategy of knowledge–based economy development in Poland.